Effect of First Language Component-Bridging Program (FLC-BP) Approach on Secondary Students’ MACRO Skills - Pamittan, Filemon A. (JPAIR Multidisciplinary Research, 2013)
The First Language Component-Bridging Program (FLC-BP) methodology calls for teaching the skills in reading, writing and math concepts in the first language. One major principle of FLC-BP is a child’s cultural model of the world which helps him process perceptual information, understand concepts and form new ones. New concepts and skills are built on existing knowledge and structures rather than bypassing them by using a rote memorization methodology. The study was undertaken to find out the effects of the First Language Component-Bridging Program on the Performance of Junior High School Learners in their Four MACRO Skills. The study adopted the quasi experimental design, specifically the Pre-test Posttest Control Group Factorial Design. Three sections of Junior High School students were utilized as respondents and assigned to Tagalog-English, Iloko-English, and English-English teaching approaches. After four months of study, the researcher found out that students exposed to the English-English approach indicated a high level of performance in listening, moderate in speaking and reading and low in writing skill. The Tagalog-English and Iloko-English showed a high level of performance in listening. Tagalog-English indicated a high level of performance in speaking and reading and moderate in writing. The Iloko-English students were moderate in speaking, reading and writing skills. Furthermore, English-only used as a medium of instruction is not the best solution to learn to speak and use English as the ladder to success. Hence, the researcher recommended the use of first language to improve the performance of students in learning.
Keywords: Socio Linguistics; First Language Component-Bridging Program; Mother Tongue Based-Multilingual Education; Macro Skills; Factorial Design; Philippines